TINJAUAN APLIKASI FISIKA RADIASI DALAM KESEHATAN DAN PEMANFAATAN RADIASI PADA BIDANG KEDOKTERAN - Ramacos Fardela; Innes Andriani; Adinda Putri; Rika Analia; Fiqi Diyona (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
In the decade between Roentgen’s discovery of X-rays in 1895 and Dr. Leonard had a lot going on in the world of radiation physics. Despite recent discoveries, especially radioactivity, the overall emphasis is on applying “Radiation” to clinical problems without fully understanding the nature of “radiation” or its interactions with matter, especially tissues. The use of x-rays discovered by William Rontgen in 1895 for medical purposes began when he found an image of his wife’s hand produced from x-rays. In this picture you can clearly see the bones in the fingers. After the discovery of x-rays, French scientist Henri Becquerel discovered another form of penetrating light—natural glow or radioactivity. The use of radiation in the medical field provides many benefits in overcoming health problems including radiodiagnostics, radiotherapy and nuclear medicine.